Flows of capital and flows of water: the textile industry and the privatisation of the water supply in Sabadell in the second half of the 20th century - Eduard Masjuan; Hug March Corbella; David Saurí Pujol (Boletín de la Asociación de Geógrafos Españoles)
Resumen